Beta2 Oscillations in Hippocampal-Cortical Circuits During Novelty Detection - França, Arthur S. C.; Borgesius, Nils Z.; Souza, Bryan C.; Cohen, Michael X. (Frontiers in Systems Neuroscience, 2021)
Novelty detection is a core feature of behavioral adaptation, and involves cascades of neuronal responses – from initial evaluation of the stimulus to the encoding of new representations – resulting in the behavioral ability to respond to unexpected inputs. In the past decade, a new important novelty detection feature, beta2 (~20 - 30 Hz) oscillations, has been described in the hippocampus. However, the interactions between beta2 and the hippocampal network are unknown, as well as the role – or even the presence – of beta2 in other areas involved with novelty detection. In this work, we combined multisite local field potential (LFP) recordings with novelty-related behavioral tasks in mice to describe the oscillatory dynamics associated with novelty detection in the CA1 region of the hippocampus, parietal cortex and mid-prefrontal cortex. We found that transient beta2 power increases were observed only during interaction with novel contexts and objects, but not with familiar contexts and objects. Also, robust theta-gamma phase-amplitude coupling was observed during the exploration of novel environments. Surprisingly, bursts of beta2 power had strong coupling with the phase of delta-range oscillations. Finally, the parietal and mid-frontal cortices had strong coherence with the hippocampus in both theta and beta2. These results highlight the importance of beta2 oscillations in a larger hippocampal-cortical circuit, suggesting that beta2 plays a role in the mechanism for detecting and modulating behavioral adaptation to novelty.